Chimeric supramolecular synthons in Ph2Te2(I2)Se. Issue 6 (18th May 2020) - Torubaev, Yury V.
Abstract : Iodination of Ph2 Te2 Se by molecular iodine is directed towards the Te atom and yields PhTeSeTeI2 Ph. The molecule can be considered as a chimera of PhTeSe R, PhTeSeTePh and R ′TeI2 Ph fragments. The energies of the intermolecular interactions have been calculated and analyzed. Abstract : Iodination of Ph2 Te2 Se by molecular iodine is directed towards the Te atom and yields diiodo[(phenyltellanyl)selanyl]‐λ 4 ‐tellanylbenzene, PhTeSeTeI2 Ph or C12 H10 I2 SeTe2 . The molecule can be considered as a chimera of PhTeSe R, PhTeSeTePh and R ′TeI2 Ph fragments. The crystal structure features a complex interplay of the supramolecular synthons Te…π(Ph), Se…Te and I…Te, combining molecules into a three‐dimensional framework. Their combination affords long‐range supramolecular synthons which are fused in a way resembling the mythological chimera and could be defined as chimeric supramolecular synthons . The energies of the intermolecular interactions have also been calculated and analyzed.